Stress among undergraduate Pokhara university business students in Kathmandu - Khadka, Bhawana (Nepalese Journal of Finance, 2025)
This study examines on the stress among undergraduate Pokhara University business students in Kathmandu. Stress among undergraduates is the dependent variable. The selected independent variables are career problem, time limit, fear of public speaking, financial difficulties and decision-making confusion. The study is based on the primary data with 139 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the stress among undergraduate Pokhara University business students in Kathmandu. The study showed that career problem is positively correlated to stress among undergraduate students. It means that higher the career problem higher will be the stress among the undergraduates. Similarly, time limit is positively correlated to stress among undergraduates. It means limited time can increase the level of stress among the undergraduates. Likewise, Fear of public speaking is positively correlated to stress among undergraduates. It reveals that as the level of fear of public speaking increases, the level of stress also tends to increase. Moreover, financial difficulties are positively correlated to stress among the undergraduates. It indicates that as financial difficulties increase among undergraduates, their stress levels tend to rise as well. In addition, decision making confusion is positively correlated to stress among the undergraduate. It means that as undergraduates experience more confusion in their decision-making, their stress levels tend to increase.